Growth, yield and agronomic efficiency of rice (Oryza sativa L.) cv. IAPAR 117 affected by nitrogen rates and sources (2017)
The aim of this research was to evaluate two traditional N sources (urea and ammonium sulfate) and an alternative one (sulfamoo) with increasing rates (0, 40, 80, 120 and 160 kg N ha-1, respectively) affecting aspects of upland rice crop cv. IAPAR 117. The experiment was carried out in greenhouse conditions, using a completely randomized design in 3x4 factorial scheme, with four replicates. It was evaluated the number of tillers (NT), plant mean height (PMH), dry matter of shoots (DMS), crop yield/mass of filled grains (MFG), content of N-DMS, agronomic efficiency of nitrogen (AE), mass of 100 filled grains (M100FG) and grain harvest index (GHI). The nitrogen rates application as ammonium sulfate resulted in a greater increasing of NT, DMS, MFG and N-DMS, respectively. In fact, higher agronomic efficiency obtained with urea and sulfamoo at 40 kg N. ha-1, although AE decreased within the higher rates of N, independently from the source. The M100FG and GHI were higher when sulfamoo and urea were used, although the high N supply negatively affected these two variables for all N evaluated sources.